2018
DOI: 10.7554/elife.38611
|View full text |Cite
|
Sign up to set email alerts
|

The decoration of specialized metabolites influences stylar development

Abstract: Plants produce many different specialized (secondary) metabolites that function in solving ecological challenges; few are known to function in growth or other primary processes. 17-Hydroxygeranylinalool diterpene glycosides (DTGs) are abundant herbivory-induced, structurally diverse and commonly malonylated defense metabolites in Nicotiana attenuata plants. By identifying and silencing a malonyltransferase, NaMaT1, involved in DTG malonylation, we found that DTG malonylation percentages are normally remarkably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 74 publications
0
33
0
Order By: Relevance
“…Primary metabolites that are associated with essential cellular functions, e.g., nucleotides, amino acids, fatty acids, sugars, and organic acids, which are typically present in all organisms and cells. In addition, organisms also produce numerous specialized (secondary) metabolites that are not essential to basic physiological functions, but otherwise play important roles during specific growth and developmental stages, and aid in adapting and adjusting the developmental need of the plant with specific physiological or environmental signals (Witzany, 2006;Tissier et al, 2014;Moghe and Last, 2015;Wurtzel and Kutchan, 2016;Li et al, 2018). Specialized compounds produced in plants were shown to have key roles in defense mechanisms, in inter-or intracellular signaling, coloring, regulation of primary metabolism, as well as in allelochemisrty (i.e., biomolecules produced by one organism that have a physiological effect on another species when released to the environment) (Rizvi and Rizvi, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Primary metabolites that are associated with essential cellular functions, e.g., nucleotides, amino acids, fatty acids, sugars, and organic acids, which are typically present in all organisms and cells. In addition, organisms also produce numerous specialized (secondary) metabolites that are not essential to basic physiological functions, but otherwise play important roles during specific growth and developmental stages, and aid in adapting and adjusting the developmental need of the plant with specific physiological or environmental signals (Witzany, 2006;Tissier et al, 2014;Moghe and Last, 2015;Wurtzel and Kutchan, 2016;Li et al, 2018). Specialized compounds produced in plants were shown to have key roles in defense mechanisms, in inter-or intracellular signaling, coloring, regulation of primary metabolism, as well as in allelochemisrty (i.e., biomolecules produced by one organism that have a physiological effect on another species when released to the environment) (Rizvi and Rizvi, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The impressive structural diversity of HGL-DTGs in N. attenuata plants results largely from glycosylation and malonylation reactions. While all malonyl decorations are instantaneously lost in the alkaline pH environment of the midgut of M. sexta larvae and therefor may play more important roles in planta (Poreddy et al, 2015;Li et al, 2018), glycosylation leads to a constant and stable pool of potential defensive compounds. Larvae feeding on leaf disks of transgenic IRggpps plants grow larger than larvae feeding on WT leaves, indicating that the overall abundance of HGL-DTGs is a major factor of the plant's resistance against M. sexta (Figure 9), consistent with earlier studies (Jassbi et al, 2008;Heiling et al, 2010;Jassbi et al, 2010).…”
Section: Defensive Function Of Hgl-dtgsmentioning
confidence: 99%
“…However, the enzymes necessary for further hydroxylation and glycosylation steps, which determine most of the structural diversity of HGL-DTGs, remain to be characterized. Li and colleagues (Li et al, 2018) identified and silenced a malonyltransferase (NaMAT1), which is responsible for the malonylation of HGL-DTGs. However, all malonyl moieties of HGL-DTGs are rapidly lost when leaves are ingested by M. sexta larvae, suggesting that the malonylation of HGL-DTGs does not play a central role in anti-herbivore defense (Poreddy et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tagging of natural products is often involved in signaling for the plant, e. g. in response to attack by herbivores, such as insects. Malonylation of secondary metabolites from Nicotiana attenuata , the 17‐hydroxygeranyl‐linalool diterpene glycosides (DTGs), was found to increase upon insect feeding, a response that is thought not to act as defense mechanism, since the malonyl residues were demonstrated to be removed upon ingestion in herbivores, suggesting a different role . Malonylated PBs have been identified, amongst others, in Nicotiana rustica and Brassica napus .…”
Section: Beyond Chlorophyll Detoxification – Potential Bioactivities mentioning
confidence: 99%